Pengembangan Modul Fixed Asset Pada Sistem Informasi Berbasis Web pada PT Prima Solusi Computindo (RADSOFT) - Firmansyah, Ferry Andika; Nuriantoro, Fajar Rizki; Putra, Andreas Bayu; Haryono, Wasis (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
PT. Prima Solusi Computindo (Radsoft) faces challenges in managing fixed assets, resulting in inefficiencies due to manual and non-integrated record-keeping processes. This study aims to design and implement a web-based information system for fixed asset management to enhance efficiency and accuracy. This system was developed using the HTML,CSS,Javascript, database SQL, and the C# framework .The research utilizes the Waterfall development model, encompassing requirements analysis, system design, implementation, and testing phases. The results indicate that the developed system effectively integrates asset management processes, including record-keeping, depreciation tracking, and reporting. This integration simplifies decision-making for the management team regarding asset utilization. Additionally, the web-based system enables real-time access across departments, improving transparency and data accuracy. As a recommendation, the company should provide training for system users to maximize the features available. Future developments may include integrating the system with other modules, such as accounting and inventory, to enhance its overall functionality.